Total recognition discriminability in Huntington's and Alzheimer's disease. Issue 2 (7th February 2017) - Graves, Lisa V.; Holden, Heather M.; Delano-Wood, Lisa; Bondi, Mark W.; Woods, Steven Paul; Corey-Bloom, Jody; Salmon, David P.; Delis, Dean C.; Gilbert, Paul E.
ABSTRACT: Both the original and second editions of the California Verbal Learning Test (CVLT) provide an index of total recognition discriminability (TRD) but respectively utilize nonparametric and parametric formulas to compute the index. However, the degree to which population differences in TRD may vary across applications of these nonparametric and parametric formulas has not been explored. We evaluated individuals with Huntington's disease (HD), individuals with Alzheimer's disease (AD), healthy middle-aged adults, and healthy older adults who were administered the CVLT–II. Yes/no recognition memory indices were generated, including raw nonparametric TRD scores (as used in CVLT–I) and raw and standardized parametric TRD scores (as used in CVLT–II), as well as false positive (FP) rates. Overall, the patient groups had significantly lower TRD scores than their comparison groups. The application of nonparametric and parametric formulas resulted in comparable effect sizes for all group comparisons on raw TRD scores. Relative to the HD group, the AD group showed comparable standardized parametric TRD scores (despite lower raw nonparametric and parametric TRD scores), whereas the previous CVLT literature has shown that standardized TRD scores are lower in AD than in HD. Possible explanations for the similarity in standardized parametric TRD scores in the HD and AD groups in the present study are discussed, with an emphasis on the importance of evaluating TRD scores in the context of other indices such as FP rates in an effort to fully capture recognition memory function using the CVLT–II.